Strengthening Economic and Development Relations Transformation Efforts Towards Golden Indonesia 2045 - Intan Zahira; M. Zidny Nafi' Hasbi; Shikur Faris (IAIN Syekh Nurjati Cirebon, 2024)
Indonesia is a country that has a big vision and mission to transform into a developed country both socially, economically, in governance, legally, and in development. As a country that has a big vision and mission, of course, Indonesia needs to build and transform to realize the country's expected future. To achieve this vision and mission, Indonesia needs special attention in various aspects to achieve the country's goals. Development and the economy are two concepts that are interrelated and inseparable. The economy functions as the main foundation of development, namely a means to achieve economic goals such as improving people's welfare. Stable and inclusive economic growth that can raise living standards and generate high-quality jobs must go hand in hand with this development. This research is qualitative, so this study provides an overview of the research topic. The purpose is to provide an overview and analysis of Indonesia's economic and development trends. This article uses secondary data sources for its data collection, using a literature study approach, information on the development economy, especially in Indonesia, is investigated. All information collected from various sources is checked and evaluated about the current state of Indonesia's development and economy. Social development must not only improve the living standards of everyone in society but also provide solutions to problems resulting from development that are not implemented properly. The goal of social development is not limited to the population as a whole, but rather how the population can develop or increase its capacity to meet its needs, goals, and desires. So to face challenges and take advantage of opportunities in the development economy, collaboration between the government, the private sector, and civil society is needed. Investments in education, infrastructure, and technological innovation are key to achieving calculated and sustainable economic growth.